2015
DOI: 10.1155/2015/743263
|View full text |Cite
|
Sign up to set email alerts
|

The Arclight Ophthalmoscope: A Reliable Low-Cost Alternative to the Standard Direct Ophthalmoscope

Abstract: Background. The Arclight ophthalmoscope is a low-cost alternative to standard direct ophthalmoscopes. This study compared the Arclight ophthalmoscope with the Heine K180 direct ophthalmoscope to evaluate its reliability in assessing the vertical cup disc ratio (VCDR) and its ease of use (EOU). Methods. Eight medical students used both the Arclight and the Heine ophthalmoscopes to examine the optic disc in 9 subjects. An EOU score was provided after every examination (a higher score indicating that the ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…In addition, Lowe et al demonstrated the AO to be as effective as the traditional direct ophthalmoscope when assessing the optic nerve head cup to disc ratio in human eyes in Tanzania. This is important in the assessment of glaucoma . Interestingly, in both of these two studies, the clinicians preferred the Arclight over the traditional device mainly because it was easier to use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Lowe et al demonstrated the AO to be as effective as the traditional direct ophthalmoscope when assessing the optic nerve head cup to disc ratio in human eyes in Tanzania. This is important in the assessment of glaucoma . Interestingly, in both of these two studies, the clinicians preferred the Arclight over the traditional device mainly because it was easier to use.…”
Section: Discussionmentioning
confidence: 99%
“…This is important in the assessment of glaucoma. 11 Interestingly, in both of these two studies, the clinicians preferred the Arclight over the traditional device mainly because it was easier to use.…”
Section: Strengths and Limitations; Comparisons With Other Studiesmentioning
confidence: 99%
“…Instruments that might be easier to use than the standard direct ophthalmoscope include the PanOptic ophthalmoscope (Welch Allyn),9 and the Arclight, a pocket ophthalmoscope 10. Another option is fundus photography, using (for example) the Peek Retina, a smart phone attachment,11 or a non-mydriatic camera 12.…”
Section: Why Is It Missed?mentioning
confidence: 99%
“…The novel features of the Arclight make it ideal for use in mobile clinics and remote low resource settings with limited access to power. Consequently over 10000 devices have been distributed, enabling thousands of health care workers worldwide to perform fundal examinations for the first time [9,28,24].…”
Section: The Arclight Devicementioning
confidence: 99%
“…vices [24]. In addition, the Arclight can be attached to the camera of a mobile phone and acquire a digital recording of the fundus for the purposes of telemedicine.…”
Section: Introductionmentioning
confidence: 99%